Construction and validation of instruments to assess school climate practices in school staff and parents - López, Verónica (2018)
The high levels of school violence reported in school institutions have made school climate a relevant issue for schools. However, while there are some instruments available that assess school climate and the perception of the school life quality, few of them assess specific practices of school climate oriented to school improvement, and even less from the perspective of school staff and parents. Through a quantitative methodological approach, in this article we present findings of the construction and psychometric analyses of two instruments that evaluate school climate practices reported by parentsand by school staff (professionals, managers, support professionals and education assistants). The validation of both instruments was carried out with a sample of 741 professionals and 1129 parents, belonging to 129 schools of different administration in Chile, under a two-stage representative sample design. Findings from reliability and confirmatory factor analyses showed suitable adjustment and reliability indicators for both instruments. Items showed a standardized estimate of .50 and coefficients of Cronbach's alpha above .7. We discuss the relevance of having instruments that allow evaluating concrete practices of school climate from the perspective of school staff and parents.